Public Expenditure Analysis - Shah, Anwar (Washington, DC: World Bank, 2012)
This book provides tools of analysis for discovering equity in tax burdens as well as in public spending and judging government performance in its role in safeguarding the interests of the poor and those otherwise disadvantaged members of society, such as women, children, and minorities. The book further provides a framework for a rights-based approach to citizen empowerment-in other words, creating an institutional design with appropriate rules, restraints, and incentives to make the public sector responsive and accountable to an average voter. Various chapters in this book provide tools of analysis for addressing the following test questions: public burden test; poverty reduction test; social protection test; gender safeguard test; responsiveness test; and accountability test.